Efficient Electrochemical Sensor Based on Gold Nanoclusters/Carbon Ionic Liquid Crystal for Sensitive Determination of Neurotransmitters and Anti-Parkinson Drugs - Nada Farouk Atta; Ahmed Galal; Ekram Hamdy El-Ads; Aya Essam Galal (Tabriz University of Medical Sciences, 2020)
Purpose: Herein we introduce a simple and sensitive sensor for the electrochemical determination of neurotransmitters compounds and anti-Parkinson drugs. Methods: The electrochemical sensor (Au/CILCE) based on gold nanoclusters modified carbon ionic liquid crystal (ILC) electrode was characterized using scanning electron microscopy and voltammetry measurements. Results: The effect of ionic liquid type in the carbon paste composite for the electro-catalytic oxidation of L-dopa was evaluated. Highest current response was obtained in case of ILC compared to other studied kinds of ionic liquids. The effective combination of gold nanoclusters and ILC resulted in extra advantages including large surface area and high ionic conductivity of the nanocomposite. L-dopa is considered one of the most important prescribed medicines for treating Parkinson's disease. Moreover, a binary therapy using L-dopa and carbidopa proved effective and promising as it avoids the short comings of L-dopa mono-therapy for Parkinson's patients. The Au/CILCE can detect L-dopa in human serum in the linear concentration range of 0.1 μM to 90 μM with detection and quantification limits of 4.5 nM and 15.0 nM, respectively. Also, the Au/CILCE sensor can simultaneously and sensitively detect L-dopa in the presence of carbidopa with low detection limits. Conclusion: The sensor is advantageous to be applicable for electrochemical sensing of other biologically electroactive species.